Conservation Facts in Nepal - Chalise, Mukesh K (The Initiation, 2010)
This short paper is critically analyzing the debate of natural resource utilization in Nepal at a new political scenario. The paper presented a view of differences against a type of intellectuals who claim the ownership of natural resources to a limited community residing in limited geography in New Nepal while neglecting majority of people who is responsible to safeguard it since ancient time. Some indigenous experiences resulted to conservation practices are also dealt as examples. Full text of this article is in Nepali. DOI: 10.3126/init.v3i0.2517 The Initiation Vol.3 2009 p.153-160